Education and the family : achievement, attainment, and quality school outcomes - Madigan, Timothy J.; Blair, Sampson Lee (Emerald Publishing Limited, 2025)
Around the world, education is regarded as an institution which can substantially aid individuals, providing them with the knowledge and skills they will need to obtain jobs, achieve financial success, and lead better lives. Across virtually all family relationships, there is an inseparable connection between education and the family. This volume of Contemporary Perspectives in Family Research is a broad examination of this correlation. The first of two connected volumes, Education and the Family: Achievement, Attainment, and Quality School Outcomes features diverse theoretical and methodological chapters which explore the interactions between two crucial institutions: the family and education system. With enormous implications for determining life outcomes, this rich edited collection on the role the familial impact on educational output and achievement. Chapters cover a wide array of topics, such as: family economic and cultural resources and school performance and attainment of students, family multilingualism and academic success, family stressors and education, valuation of higher education versus employment and family contestations of public schooling and its policies and curriculum among others. Education and the Family: Achievement, Attainment, and Quality School Outcomes is appealing reading for scholars of family sociology, the sociology of education, and childhood and youth alike.
Keywords: Education -- Parent participation.; Education -- Parent Participation.; Educational strategies and policy.; elektronické knihy; electronic books